Endoscopic surgical management of the anterior skull base by nasal cerebrospinal fluid fistula in a third level of care (Revista de Medicina Clinica, 2020)
BACKGROUND: Nasal cerebrospinal fluid (FLCR) fistulas are presented by different causes, whether traumatic, idiopathic or surgical, it is a priority to attend them before presenting complications, in recent years the endoscopic closure has gained popularity. OBJECTIVE: To evaluate the success rate of FLCR endoscopic closure in the ENT service at a third level reference centerMATERIAL AND METHODS: A retrospective study of a series of cases was carried out, we reviewed the files of post-operative patients with endoscopic closure of nasal FLCR from 2016 to 2019. The clinical and epidemiological variables related to FLCR were analyzed in all patients. We use X2 to evaluate the dichotomous categorical variables, the qualitative, nominal and ordinal variables, were interpreted by means of the calculation percentage, proportion, rate or relation. SPSS version 22.0 was usedRESULTS: We included 20 patients, 13 (65%) female sex, the ethmoidal region was the most frequent site 13 (65%), 18 (90%) hill in the first intervention, When using X2 in order to assess the relationship between success of surgery and the use of lumbar drainage, showed no significant result p = 0.891, and when evaluating the relationship of fluid fistula and comorbidities if significant results were found with a value of p = 0.040CONCLUSIONS Our study confirms a 90% success rate. The most frequent site is the ethmoidal region. In our hospital we have very similar results to the international reports, both in the diagnostic approach, surgical technique, and the final results.
Keywords: cerebrospinal fluid fistula, nasal, endoscopic treatment, success.